Marketing communication influencing buying decision of consumer in Koh-kred Market, Nonthaburi Province - พูลสวัสดิ์, กิตติพร; ถนอมเวช, ปริษฐา; นาครอด, สุริมาศ; สุภาภัทรพิศาล, ชูใจ; ยูโซะ, ยาวาเฮ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the level of opinions regarding marketing communication factors influencing consumers’ purchasing decision-making process at Koh Kret Market, Nonthaburi Province; 2) investigate the level of opinions toward the purchasing decision-making process of consumers at Koh Kret Market, Nonthaburi Province; and 3) analyze the influence of marketing communication on the consumers’ purchasing decision-making process at Koh Kret Market, Nonthaburi Province. The sample group consisted of 400 Thai tourists visiting Koh Kret Market, Nonthaburi Province. The research instrument was a questionnaire with a reliability coefficient of 0.95 The data were analyzed using mean, percentage, standard deviation, and multiple regression analysis.          The results revealed that: 1) The overall level of opinions regarding marketing communication factors at Koh Kret Market was at a high level. When considering each aspect, public relations was rated the highest, followed by event marketing, sales promotion, direct marketing, personal selling, and advertising, respectively; 2) The overall level of opinions regarding the consumers’ purchasing decision-making process was also at a high level. Among the aspects, evaluation of alternatives was rated the highest, followed by problem recognition, purchase decision, information search, and post-purchase behavior, respectively; and 3) Marketing communication significantly influenced the consumer purchasing decision-making process at Ko Kret Market, Nonthaburi Province, at the 0.05 level of statistical significance. The multiple correlation coefficient (R) was 0.986, and the coefficient of determination (R²) indicated a predictive power of 97.30%, which supported the stated hypothesis.